Fractionation mechanisms of rare earth element speciation in granitic weathering profiles: Metallogenic implications for the kuanyu ion-adsorption REE deposit, dechang, SW China - Lijun Qian; Lihua Ou; Guoxin Li; Xuepeng Xiao; Bo Qian (PLoS ONE, 2025)
The Kuanyu ion-adsorption rare earth element (REE) deposit, Sichuan’s first economically viable resource of its type, remains underexplored in terms of REE fractionation and enrichment mechanisms within its weathering profiles. This study systematically resolves REE speciation patterns and light-to-heavy REE (LREE/HREE) differentiation processes, advancing the metallogenic framework fo r such deposits. Analytical results demonstrate: (1) A vertically progressive enrichment of LREE-dominated REE concentrations from bedrock to topsoil, with the fully weathered layer serving as the primary enrichment zone; (2) Weathering of primary REE-bearing minerals and subsequent secondary mineral formation as drivers of elemental redistribution; (3) Contrasting controls by clay minerals, iron-manganese oxides, and humic acids—clay minerals preferentially adsorb LREEs, while iron-manganese oxides exhibit stronger HREE affinity through inner-sphere complexation, and humic acids enhance HREE mobility via stable complex formation. These findings establish iron-manganese oxides and organic ligands as dual regulators of REE fractionation, refining predictive models for ion-adsorption REE exploration in granitic weathering systems.